Trash, dirt, glitch: The imperfect turn. (February 2023) - Rutten, Ellen; de Vos, Ruby
'Trash, dirt, glitch' offers an introduction to a cluster devoted to trash, dirt and glitch – concepts that, in aesthetic and artistic domains, firmly merit joint exploration. In fashion and urban design, music, art and other aesthetic practices, the trashy, the dirty and the glitchy interconnect in complex choreographies, in discourses and practices where they are framed as benefit rather than bother. For this cluster, the authors asked four scholars in media, design and fashion to examine the interconnections between trash, dirt and glitch as affirmatively charged categories. They do so through in-depth studies of 'dirt(y)' and glitch-based sound-making practices and media art in Australia (Caleb Kelly); German electronic and glitch music (Jakko Kemper); dirt and trash aesthetics in sneaker fashion and (especially but not only) US-based grunge subcultures (Ekaterina Kulinicheva); and discourses of dirt and disorder in the creative industry in Russia (Margarita Kuleva). This introduction contextualizes their findings and offers tools to theorize the present-day interest in dirt-, trash-, and glitch-based aesthetics as an imperfect turn. This turn we envision not as an unprecedented shift, but as the latest in a series of socio-technologically motivated historical imperfect turns. The imperfect turn that we witness today is not without its flaws – but, as we argue below, it can facilitate important social interventions.